The Effect of Biaxial Strain on The Thermoelectric Properties of 2D SiBi - Anshory, Muhammad; Y. Hanna, Muhammad (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
This study investigates the electronic and thermoelectric properties of two-dimensional silicon bismuth (2D SiBi) using first-principles Density Functional Theory (DFT) calculations. The 2D SiBi monolayer is identified as a semiconductor with an indirect band gap of 0.67 eV. Solving the Boltzmann transport equation reveals outstanding thermoelectric performance, evidenced by high Seebeck coefficients of 1243.79 µV/K (p-type) and 1217.23 µV/K (n-type) at room temperature. Most significantly, the application of a modest -1% biaxial compressive strain induces a substantial enhancement in these values, elevating them to 1361.75 µV/K and 1371.85 µV/K for p-type and n-type carriers, respectively. These results demonstrate that mechanical strain is an effective strategy for tuning and optimizing the thermoelectric efficiency of 2D SiBi, positioning it as a highly promising material for next-generation thermoelectric devices.